Failure of Cone-Beam Computed Tomography in Detection of Fiber Post Perforation - Fazlyab, Mahta; Asgary, Saeed (Iranian Endodontic Journal, 2017)
Detection of iatrogenic root perforation during post-space preparation especially in labiolingual plane can be challenging due to the two-dimensional nature of conventional radiography; this can be even more challenging if the cemented post is radiolucent. Cone-beam computed tomography (CBCT) scans were shown to be a valuable diagnostic aid in diagnosis of such cases. However, in this case, the application of CBCT did not help in diagnosis of a labial fiber post perforation in a maxillary central incisor which was finally detected through exploratory surgery. Keywords: Calcium-Enriched Mixture; Cone-Beam Computed Tomography; Diagnosis; Post Space Preparation; Root Perforation